USP37-stabilized SALL4 promotes the keloid formation by PI3K/AKT pathway - Shuo Fang; Zishuo Wang; Jianguo Xu; Miao Xu; Jiesong Zhou; Yuntong Zhang; Chunyu Xue (Scientific Reports)
Abstract Spalt-like transcription factor 4 (SALL4) plays a vital role in the progression of many human diseases. However, the role and mechanism of SALL4 regulates in keloid formation remain unclear. The mRNA levels of SALL4 and ubiquitin-specific peptidase 37 (USP37) in keloid tissues and keloid fibroblasts were determined by quantitative real-time PCR. Western blot was performed to measure the protein levels of SALL4, USP4/10/37, collagen-related markers, and PI3K/AKT-related markers. The growth, invasion and migration of keloid fibroblasts were determined using CCK8 assay, EdU assay, flow cytometry, transwell assay and wound healing assay. Cell glycolysis was assessed by detecting glucose consumption and lactate production. The interaction between USP37 and SALL4 was confirmed by co-immunoprecipitation assay. SALL4 had increased expression in keloid tissues and keloid fibroblasts. Silencing of SALL4 inhibited the growth, invasion, migration, extracellular matrix (ECM) accumulate and glycolysis of keloid fibroblast, while its overexpression had the opposite effects. In terms of mechanism, USP37 stabilized SALL4 expression through deubiquitinating. Functional experiments suggested that SALL4 overexpression reversed the inhibitory effect of USP37 knockdown on keloid fibroblast functions. Moreover, USP37/SALL4 axis could increase the activity of PI3K/AKT pathway, and PI3K pathway inhibitor LY294002 abolished SALL4-mediated the promoting on keloid fibroblast functions. USP37-activated SALL4 might enhance keloid fibroblast growth, invasion, migration, ECM accumulation and glycolysis via activating PI3K/AKT pathway.